Board Dynamics and Tax Aggressiveness: Unveiling the Power of Gender Diversity - Wulandari, Dian Sulistyorini; Widati, Sindik; Diyah Permatasari, Maulina (Journal of Applied Accounting and Taxation, 2026)
This study examines the influence of the board of directors and independent commissioners on corporate tax aggressiveness, with gender diversity considered as a moderating variable. The research aims to determine whether board structure affects corporate tax strategies and whether the presence of female board members strengthens or weakens these relationships. A quantitative approach is employed using panel data regression analysis based on a sample of publicly listed companies. Data are collected from corporate financial reports and governance disclosures. Several model selection procedures are applied to identify the most appropriate regression model, followed by hypothesis testing using panel data estimation techniques. The findings indicate that the board of directors does not have a significant effect on tax aggressiveness, suggesting that board size alone does not determine corporate tax planning decisions. In contrast, independent commissioners show a significant positive effect on tax aggressiveness, implying that their presence may be associated with more aggressive tax strategies rather than stronger oversight. Furthermore, gender diversity does not moderate the relationship between either the board of directors or independent commissioners and tax aggressiveness, indicating that female representation on the board does not significantly influence corporate tax behavior. These results suggest that regulatory bodies need to strengthen governance mechanisms to ensure that independent commissioners effectively perform their monitoring role. Companies are encouraged to emphasize board competence and expertise rather than relying solely on structural characteristics such as size or gender composition. Greater transparency in corporate tax practices is also recommended for investors and stakeholders. This study contributes to the literature by highlighting the limited role of board size and gender diversity in tax decision-making, while indicating that independent commissioners may not always function as effective governance mechanisms in reducing tax aggressiveness.